Optimal implementation of lightweighting and powertrain effi ciency technology in passengers' vehicles - Wilhelm, Erik; Hofer, Johannes; Schenler, Warren; Guzzella, Lino (Transport, 2012)
Improving powertrain efficiency and reducing vehicle weight are two options for reducing vehicle energy use, emissions, and operating cost that often increase the purchase cost of passenger vehicles. Increasing drivetrain efficiency shrinks the potential for reducing energy use by lightweighting and conversely lighter vehicles benefit less from efficiency improvement. This paper describes a methodology for finding the optimum combination of light-weighting and efficiency measures to achieve minimum lifetime vehicle cost. Using representative technology cost assumptions for a mid-sized passenger car, marginal efficiency improvement in the range of 20 to 30% and lightweighting between 200 and 600 kg are optimal, depending strongly on marginal cost curve characteristics. A reduction in the total cost of vehicle ownership of between 18 and 42% is possible for the representative technology implementation scenarios. In the absence of reliable cost data, a general strategy of designing lightweight vehicles with lower powertrain efficiency or else higher-efficiency powertrains which are integrated in heavier vehicles is recommended.First Published Online: 19 Sep 2012